Iron status, immune system, and expression of brain divalent metal transporter 1 and dopamine receptors D1 interrelationship in Parkinson's disease and the role of grape seed and green coffee bean extracts and quercetin in mitigating the disease in rats - Sahar Youssef Al-Okbi; Hoda Bakr Mabrok; Enas Sabry K Al-Siedy; Rasha Salah Mohamed; Asmaa Abdelmohsen Ramadan (Shahrekord University of Medical Sciences, 2022)
Introduction: Parkinson's disease (PD) is a neurodegenerative disease with a prevalence of 1% in the elderly worldwide. The aim of the research is to study the interrelationship of iron status, the immune system including inflammatory cytokines, brain divalent metal transporter 1 (DMT1), and dopamine receptors D1 (DRD1) in a PD rat model. The potential protective effects of grape seed and green coffee bean ethanol extracts and quercetin were also studied. Methods: Phenolic and flavonoid contents of grape seed and green coffee bean and in vitro free radicals scavenging activities of the extracts and quercetin were determined. Male rats were divided into five groups. Group 1 served as normal control (NC), group 2 represented Parkinsonian control (PC). Groups 3, 4, and 5 were the test groups treated by daily oral green coffee bean, grape seed extracts, and quercetin, respectively. PD was induced by rotenone in groups 2 to 5. Brain oxidative stress, DMT1, and DRD1 expressions, and histopathology were assessed. Parameters of the immune system, represented by plasma interferon-gamma (IFNγ) and CD4, and brain tumor necrosis factor-alpha (TNF-α) along with iron status were also determined. Results: Phenolic and flavonoid contents of green coffee bean were high compared to grape seed (P < 0.05). Quercetin experienced the highest in-vitro free radicals scavenging activities. Iron deficiency anemia, together with elevated IFNγ, TNF-α, DMT1 expressions, and brain malondialdehyde (MDA) were demonstrated in PC compared to NC (P < 0.05). Also, reduction in CD4 and brain reduced-glutathione (GSH) (P < 0.05) were noticed in PC with brain histopathological alterations. Different treatments showed variable improvements in the majority of parameters (P < 0.05) and brain histopathology. Conclusion: Iron deficiency anemia might result from cytokine elevation in PD. Reduced DRD1 and altered immune system including cytokines together with increased brain DMT1 might induce neurodegeneration in PD. Different treatments showed variable neuroprotective effects through modulation of inflammation, oxidative stress, immune system, iron status, DMT1, and DRD1.